Fluctuación poblacional y parasitismo de larvas de capitarsia decolora guenée, plutella xylostella l. y trichoplusia ni hübner (lepidoptera) en brassica oleracea l. - Tovar Hernández, Horacio; Bautista Martínez, Néstor; Vera Graziano, Jorge; Súarez Vargas, Alma Delia; Ramírez Alarcón, Samuel (Instituto de Ecología, A.C., 2007)
Population fluctuation and percentages of parasitism were determined for Copitarsia decolora (Guenée), Plutella xylostella L. and Trichoplusia ni Hübner on three varieties of B. oleracea, cabbage, cauliflower and broccoli, from April 2004 trough April 2005, in Acatzingo, Puebla, Mexico. Every 14 days randomized samplings in 10 plants by crop were made; the total number of larvae were recorded, collected and maintained in a rearing room at 27º C ± 1º C and 75% ± 5% of relative humidity for parasitoid development. The pest population was more abundant during head formation in cabbage and pellet formation in broccoli and auliflower. The greatest density was observed in cabbage, with values of 1.3, 12.3 and 2.4 larvae by plant, for C. decolora, P. xylostella and T. ni, respectively. Diadegma insulare Cresson (Hymenoptera: Ichneumonidae) was obtained from P. xylostella larvae, whereas Voria ruralis Fállen (Diptera: Tachinidae) was obtained from T. ni larvae. The mean rate of parasitism for D. insulare was 46.78% and for V. ruralis only 0.7%. The population density and rates of parasitism were negatively affected by insecticide application on the crops of broccoli, cabbage and cauliflower.